Quasi-in situ electron backscatter diffraction analysis of twinning–detwinning behavior in AZ31 magnesium-alloy rolled plates subjected to compression loading in different directions - Le Zhou; Guiyuan Ren; Tianqi Huang; Zhi Wang; Feng Wang; Ziqi Wei; Pingli Mao; Zheng Liu (Journal of Magnesium and Alloys)
In this study, the twinning–detwinning behavior and slip behavior of rolled AZ31 magnesium-alloy plates during a three-step intermittent dynamic compression process along the rolling direction (RD) and normal direction (ND), are investigated via quasi-in situ electron backscatter diffraction, and the causes of the twinning and detwinning behavior are explained according to Schmid law, local strain coordination, and slip trajectories. It is found that the twins are first nucleated and grow at a compressive strain of 3% along the RD. In addition to the Schmid factor (SF), the strain coordination factor (m') also influences the selection of the twin variants during the twinning process, resulting in the nucleation of twins with a low SF. During the second and third steps of the application of continuous compressive strains with magnitudes and directions of 3%RD+3%ND and 3%RD+3%ND+2.5%ND, detwinning occurs to different extents. The observation of the detwinning behavior reveals that the order in which multiple twins within the same grain undergo complete detwinning is related to Schmid law and the strain concentration, with a low SF and a high strain concentration promoting complete detwinning. The interaction between slip dislocations and twin boundaries in the deformed grains as well as the pinning of dislocations at the tips of the {101¯2} tensile twins with a special structure result in incomplete detwinning. Understanding the microstructural evolution and twinning behavior of magnesium alloys under different deformation geometries is important for the development of high-strength and high-toughness magnesium alloys.